2015
DOI: 10.4038/jnsfsr.v43i2.7946
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cover soil properties of solid waste dumpsites in Colombo District, Sri Lanka

Abstract: Landfill cover soils have to serve multiple purposes such as operational safety, environmental protection, recultivation and integration of the sites into the landscape. Cover soil properties must therefore be defined with respect to the thickness, bulk density, air permeability and the available field capacity. The primary objective of this study is to examine the cover soil properties of three selected landfill sites (dumpsites) in Sri Lanka in order to propose suitable cover soil properties for similar appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…LL between the range of 30% and 35% and PI between the range of 9% and 20% was obtained by Ayininuola [20]. Furthermore, LL between the range of 24% and 38% and PI between the range of 4% and 9% was obtained by Harshani et al [21]. The low PI obtained in this study may have been due to the limited amount of clay present in the soil particles, whereas, increase observed in PI of the samples may have been caused by reduction of the effective porosity due to clogging effect of pore space as a result of increasing amount of microorganisms in the leachate.…”
Section: Resultsmentioning
confidence: 87%
“…LL between the range of 30% and 35% and PI between the range of 9% and 20% was obtained by Ayininuola [20]. Furthermore, LL between the range of 24% and 38% and PI between the range of 4% and 9% was obtained by Harshani et al [21]. The low PI obtained in this study may have been due to the limited amount of clay present in the soil particles, whereas, increase observed in PI of the samples may have been caused by reduction of the effective porosity due to clogging effect of pore space as a result of increasing amount of microorganisms in the leachate.…”
Section: Resultsmentioning
confidence: 87%
“…These have been extensively studied for loose soil suitable for agriculture (Major et al 2012;Ouyang et al 2013;de-Melo-Carvalho et al 2014;Prober et al 2014;Moragues-Saitua et al 2017;Chen et al 2019). However, limited studies are available for soil in geotechnical and geoenvironmental engineering structures, e.g., landfill cover (Wong et al 2017), bioengineered slopes and embankment (Bordoloi et al 2018b;Ni et al 2018) where soils often compacted, have higher design life and generate higher suction due to drying (Wall and Zeiss 1995;Harshani et al 2015). Wong et al (2017) reported an increased water retention of kaolin clay after amendment of peanut shell biochar.…”
Section: Introductionmentioning
confidence: 99%